IMAGE OF ELDERLY PEOPLE IN THE OPINION OF CHILDREN AT SCHOOL AGE - Olimpia Gogolin; Eugeniusz Szymik (Journal of Modern Science, 2018)
Objectives The aim of this article is to demonstrate how class I to III students see older people.